Determinasi Inflasi dan Jumlah Uang Beredar Terhadap Pertumbuhan Ekonomi di Indonesia : Penelitian - Khairani Alawiyah Matondang; Siti Khofifah Hanif; Helena Seprina Sitohang; Intan Harahap; Gebatania Pakpahan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Inflation and money supply pla y an essential role in influencing a country’s economic growth. This study aims to analyze the effect of inflation and money supply on economic growth in Indonesia from 2005 to 2024. The study uses secondary data obtained from Statistics Indonesia (BPS) and is analyzed using multiple linear regression methods. The results show that inflation has a negative but insignificant effect on economic growth, while the money supply has a positive and significant effect on Gross Domestic Product (GDP). Simultaneously, both variables significantly influence Indonesia’s economic growth. The coefficient of determination (R²) value of 0.987 indicates that 98.7% of the variation in GDP is explained by inflation and money supply. These findings highlight the importance of maintaining a balance between inflation control and liquidity management to ensure sustainable and stable economic growth in Indonesia. In addition, the results emphasize that monetary policy should be directed toward stimulating productive sectors, improving public purchasing power, and supporting investment activities. A well-coordinated policy between the government and the central bank is needed to maintain price stability while encouraging inclusive and long-term economic development.